Poole-Frenkel effect in Er doped SnO2 thin films deposited by sol-gel-dip-coating - Morais, E. A.; Scalvi, LVA; Ribeiro, SJL; Geraldo, V (Wiley-Blackwell, 2005)
Electrical properties of Er-doped SnO2 thin films obtained by sol-gel-dip-coating technique were measured. When compared to undoped tin dioxide, rare-earth doped films present much higher resistivity, indicating that Er3+ presents an acceptor-like character into the matrix, which leads to a high degree of electric charge compensation. Current-voltage characteristics, measured above room temperature for Er-doped films, lead to non-linear behavior and two conduction regimes. In the lower electric field range the conduction is dominated by Schottky emission over the grain boundary potential barrier, which presents an average value of 0.85 eV. Increasing the applied bias, a second regime of conduction is observed, since the Poole-Frenkel coulombic barrier lowering becomes a significant effect. The obtained activation energy for ionization is 0.67 eV. (C) 2005 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.